A Novel Approach to Electronic Nursing Documentation Education: Ambassador of Learning Program. Issue 6 (November 2019) - Malane, Elizabeth A.; Richardson, Cynthia; Burke, Kathleen G.
Abstract : Health care is rapidly evolving to meet the changing needs of our increasing complex patients. Nursing practice must keep pace with these changes. Emerging information technologies such as electronic health records (EHRs) challenge nursing practice to redesign workflow. Providing nurses with effective education on how to incorporate EHR documentation is essential for safe patient care. This article describes the development of an education program that promotes accurate and more efficient nursing EHR documentation practices.